The Role of Internal Audit and Risk-Based Audit in Improving Local Government Financial Accountability - Sofa, Aulia Rizka; Marbun, Nancy; Sembiring, Dealova Venolika Br; Sebayang, Vivi Febyani; Nst, Dito Aditia Darma (EDUCTUM: Journal Research, 2025)
This study aims to analyze the role of internal audit and the implementation of risk-based audits in improving local government financial accountability. Internal audit serves as a supervisory instrument that ensures regional financial management is carried out in accordance with the principles of transparency, efficiency, and regulatory compliance, while risk-based audits emphasize the identification and mitigation of key risks that have the potential to hinder the achievement of organizational goals. This study uses a qualitative approach with a conceptual-descriptive method through a literature review of laws and regulations, public sector audit standards, and relevant previous research findings. The analysis results indicate that the synergy between effective internal audit and the implementation of risk-based audits can strengthen the internal control system, improve the quality of supervision, and minimize the potential for irregularities in regional financial management. In addition, the use of information technology through the implementation of e-audit and digital data analysis contributes to increasing the efficiency, accuracy, and transparency of the audit process. Thus, the combination of internal audit and risk-based audit is a strategic instrument in realizing accountable, transparent, and integrity-based local government financial governance.